Mycobacterium chimaera Genomics With Regard to Epidemiological and Clinical Investigations Conducted for an Open Chest Postsurgical Mycobacterium chimaera Infection Outbreak. (16th April 2021) - Lecorche, Emmanuel; Daniau, Côme; La, Kevin; Mougari, Faiza; Benmansour, Hanaa; Kumanski, Sylvain; Robert, Jérôme; Fournier, Sandra; Lebreton, Guillaume; Carbonne, Anne; Cambau, Emmanuelle; ,
Abstract: Background: Postsurgical infections due to Mycobacterium chimaera appeared as a novel nosocomial threat in 2015, with a worldwide outbreak due to contaminated heater-cooler units used in open chest surgery. We report the results of investigations conducted in France including whole-genome sequencing comparison of patient and heater-cooler unit isolates. Methods: We sought M. chimaera infection cases from 2010 onwards through national epidemiological investigations in health care facilities performing cardiopulmonary bypass, together with a survey on good practices and systematic heater-cooler unit microbial analyses. Clinical and heater-cooler unit isolates were subjected to whole-genome sequencing analyzed with regard to the reference outbreak strain Zuerich-1. Results: Only 2 clinical cases were shown to be related to the outbreak, although 23% (41/175) of heater-cooler units were declared positive for M. avium complex. Specific measures to prevent infection were applied in 89% (50/56) of health care facilities, although only 14% (8/56) of them followed the manufacturer maintenance recommendations. Whole-genome sequencing comparison showed that the clinical isolates and 72% (26/36) of heater-cooler unit isolates belonged to the epidemic cluster. Within clinical isolates, 5–9 nonsynonymous single nucleotide polymorphisms were observed, among which an in vivo mutation in a putative efflux pump gene was observed in a clinical isolate obtained for 1 patient on antimicrobial treatment. Conclusions: Cases of postsurgical M. chimaera infections have been declared to be rare in France, although heater-cooler units were contaminated, as in other countries. Genomic analyses confirmed the connection to the outbreak and identified specific single nucleotide polymorphisms, including 1 suggesting fitness evolution in vivo.